2013
DOI: 10.1080/13549839.2012.688735
|View full text |Cite
|
Sign up to set email alerts
|

“Carbon literacy practices”: textual footprints between school and home in children's construction of knowledge about climate change

Abstract: This paper examines the notion of "carbon literacy practices" through reporting on a small research project aimed at understanding how children make sense of climate change, and their subsequent related practices at school, at home, and in the community. Drawing on a background in New Literacy Studies (e.g. Barton et al 2000;Satchwell &Ivanic 2009 and2010), the paper explores the relationships among children"s understanding of climate change, their literacy practices in relation to climate change, and their en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 20 publications
0
28
0
1
Order By: Relevance
“…Increased knowledge of climate change does not automatically mean a young person will turn the lights off at home, nor does it mean that children asking their parents to change their behavior will result in parents actually changing their practices (Satchwell 2012). However, we are simultaneously seeing increasing scholarly support for the potential of schools as promising spaces for community-focused and multigenerational learning opportunities (Uzzell 1994;Leeming et al 1997;Waddock and Freedman 1998/99;Ballyntyne et al 2000;Peterat and Mayer-Smith 2006;Léger 2013;Wyness 2013;Percy-Smith and Burns 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Increased knowledge of climate change does not automatically mean a young person will turn the lights off at home, nor does it mean that children asking their parents to change their behavior will result in parents actually changing their practices (Satchwell 2012). However, we are simultaneously seeing increasing scholarly support for the potential of schools as promising spaces for community-focused and multigenerational learning opportunities (Uzzell 1994;Leeming et al 1997;Waddock and Freedman 1998/99;Ballyntyne et al 2000;Peterat and Mayer-Smith 2006;Léger 2013;Wyness 2013;Percy-Smith and Burns 2013).…”
Section: Introductionmentioning
confidence: 97%
“…She observed that some ‘pro‐environmental’ practices were confined to or associated with particular spaces, for example, composting in gardening projects at school or using renewable energy at home. In findings that resonate with the work of Shove and others (), Satchwell (, p. 297) suggests that the different ‘configurations of elements’ in particular spaces — the materials available to children, the meanings of particular practices current in these spaces and the competences involved in carrying out practices in particular ways — might account for the way in which such practices did not always travel with children across spaces.…”
Section: Children's Responses To Environmental Education Messagesmentioning
confidence: 82%
“…Social theorists have drawn attention to the rationalist assumptions of individual agency embedded in this governance model in ways ‘so pervasive as to seem natural’, often through an ‘ABC’ model of social change, where A stands for Attitude, B for behaviour and C for Choice (Shove and others, , p. 2). According to this logic, educating the public about environmental problems will cause them to change their behaviours (Satchwell, ). Scholars have critiqued these assumptions for their limited attention to the complexity of the social world and the structures in which individuals operate (Hobson, ; Middlemiss, ; Shove, ).…”
Section: Continuities Of Environmental Governance: Connecting Local Amentioning
confidence: 99%
See 1 more Smart Citation
“…Through the Decade of Education for Sustainable Development (2005-14), led by the UNESCO, governments have been called to 'integrate the principles, values and practices of sustainable development into all aspects of education and learning' so that students around the world may 'learn the values, behaviour and lifestyles required for a sustainable future and for positive societal transformation' (UNESCO, undated). As a result, recent years have seen the introduction of initiatives including Sustainable Schools and Eco-schools in the UK (Evans and Honeyford, 2012;Satchwell, 2013) and the National Green Corps in India (Ravindranath, 2007). These policy framings indicate that children, as the 'next generation', are expected to play a central role in climate change practices.…”
Section: Futurity Families and Childrenmentioning
confidence: 99%